2021
DOI: 10.1177/23220937211059617
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Authentic Leadership in Shaping Performance Feedback Reactions: The Mediating Role of Trust in Leader

Abstract: In this study we attempted to explore the effect of authentic leadership on followers’ feedback reactions in the performance appraisal context using trust in leader as the mediating variable. We collected data from a sample of 183 employees working in the information technology sector of Pakistan using a self-administered questionnaire, employing a cross-sectional study design with convenience sampling technique. The study provided empirical evidence about the effect of authentic leadership on performance feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…In addition, a study by Chen and Sriphon (2022) indicated that authentic leadership was linked positively to social exchange relationships and trust. Furthermore, an authentic leadership style can promote a healthy and supportive work setting characterized by sound relationships and trust among team members, follower trust in their leaders (Asad et al, 2021) and their organization (Alkaabi, 2018;Kleynhans et al, 2021a). Thus, it is plausible to argue that increased levels of trust can be ascribed to the example of authentic leaders characterized by high moral standards, honesty, transparency, and integrity.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…In addition, a study by Chen and Sriphon (2022) indicated that authentic leadership was linked positively to social exchange relationships and trust. Furthermore, an authentic leadership style can promote a healthy and supportive work setting characterized by sound relationships and trust among team members, follower trust in their leaders (Asad et al, 2021) and their organization (Alkaabi, 2018;Kleynhans et al, 2021a). Thus, it is plausible to argue that increased levels of trust can be ascribed to the example of authentic leaders characterized by high moral standards, honesty, transparency, and integrity.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…However, we suggest this negative feedback provision activity can impede employee learning performance when it is frequently adopted. This is because employees become less motivated to distill information that enables them to improve their performance from negative feedback as their degree of trust in their supervisor decreasesafter all, employees with low levels of trust in their supervisor tend not to rely on their feedback (Asad et al, 2022). In addition, the low trust caused by frequent negative feedback can make employees' unwilling to be committed to the learning goal set by their supervisors because they are less motivated to strive to meet their supervisors' expectations (Bektas ¸et al, 2022;Khattak et al, 2020).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…However, we suggest this negative feedback provision activity can impede employee learning performance when it is frequently adopted. This is because employees become less motivated to distill information that enables them to improve their performance from negative feedback as their degree of trust in their supervisor decreases – after all, employees with low levels of trust in their supervisor tend not to rely on their feedback (Asad et al. , 2022).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Leadership is one of the most important researched areas within old and recent literature [15,16,50]. As the ultimate goal of the largest variety of creative oriented companies [51], the sustainable competitive advantage could be the result of a healthy knowledge-sharing organizational culture mechanism, namely transformational leadership and followers' performance. While largely untested [52], transformational leadership theories suggest that its effects widely vary in accordance with the extremities of the business environments in which it is exercised.…”
Section: Transformational Leadership Theoretical Specificitiesmentioning
confidence: 99%